Collision course : the Cuban missile crisis and coexistence - Pachter, Henry Maximilian, 1907-1980. (New York : Praeger, 1963)
"Although we live in a world of swiftly moving events, and although many of yesterday's banner headlines are forgotten today, U.S. policy toward Cuba continues to play a major role on the world political scene and remains the subject of lively, at times acrimonious, political debate. Thus Dr. Pachter's provocative hour-by-hour, issue-by-issue recapitulation of the missile crisis of October-November, 1962, constitutes a timely and important chapter in the annals of contemporary history. This book is a closely reasoned inquiry into and analysis of the motives, considerations, personalities, and objectives that determine U.S. policy in the Caribbean. And, perhaps most important, it provides a perspective often lacking in political debate--an examination of American policy in terms of a more general discussion of the forces that govern international power conflicts, the "ground rules" of coexistence that statesmen must observe in order to maintain peace. But the significance of this carefully documented and revealing work goes far beyond the great political debate over Cuba. Dr. Pachter has written, in effect, a classic case study in the international relations of a world poised on the brink of war. In the extensive appendix, the author has compiled the texts of all the documents pertaining to the missile crisis: the historic texts that have defined American policy in Latin America since the Monroe Doctrine; the major statements of Castro, Kennedy, Khrushchev, Mao Tse-tung, U Thant, and Dortic os; and all the diplomatic correspondence and resolutions of October and November, 1962"--Jacket.
Two weeks of crisis. The alarm ; The intelligence report ; The war council ; The Kennedy style ; The President goes campaigning ; Gromyko pays a visit ; Decision ; Hesitation--reflection--justification ; Profile in courage ; World opinion wonders ; The Monroe Doctrine revived ; Diplomatic charade ; Blockade ; United Nations Day ; Stevenson becomes impatient ; Khrushchev writes a letter ; The War Council makes a decision ; On the brink ; Surrender -- Results and assumptions. Khrushchev ; Castro ; Kennedy ; Dissent ; U Thant -- Principles of coexistence. The law of polarization ; The Soviet conception of coexistence ; Ideology and raison d'etat ; Coexisting with capitalism ; Ground rules for coexistence ; Recapitulation: the new "zag" -- Appendixes. A chronology of United States-Cuban relations ; Documents of United States policy toward Latin America and on international law governing blockade ; Documents on inter-American security ; Documents relating to the Missile Crisis, October, 1962.
Includes bibliographical references and index.
NLJCols20082021
Keywords: Cuban Missile Crisis, 1962.; United States -- Foreign relations -- 1961-1963.; Military bases, Soviet -- Cuba; World politics -- 1955-1965.; Diplomatic relations; Military bases, Soviet; World politics; Cuba; United States; Cuban Missile Crisis, 1962.; United States -- Foreign relations -- 1961-1963.; United States -- Foreign relations -- Cuba; 1955-1965